Good writer's guide (Journal of Parents and Teachers, 2014)
The writing process is something complex that involves following a few steps or a guided structure for its correct realization, because it accompanies the student throughout their school period and determines their school success. Therefore, you must follow a prior planning, a written supervision and an evaluation of the work with a series of indications, in each of them, that will make up the final text and its correct purpose or message.
Keywords: writing; process; writer; before; during; after; revision; planned; supervised; evaluated